Prevalence of atrial myopathy among hypertrophic cardiomyopathy patients without atrial fibrillation. (3rd October 2022) - Pagourelias, E; Boulmpou, A; Evangeliou, A; Zormpas, G; Alexandridis, G; Kotzadamis, D; Vergopoulos, S; Tsavousoglou, C; Antoniadis, A; Mavroudi, M; Papadopoulos, C E; Tzikas, S; et al.
Abstract: Background: Atrial myopathy (AM) is an entity reflecting left atrial (LA) structural and electrical remodeling, connected to atrial fibrillation (AF) development and heart failure progression in various substrates. In hypertrophic cardiomyopathy (HCM), prevalence of AM beyond AF and its correlations are not fully investigated. Purpose: Aim of this study was to estimate the prevalence of AM in a cohort of HCM patients without AF history through assessment of LA volume index (LAVI), LA reservoir strain (LARS) and total atrial conduction time (TACT) (estimated by tissue Doppler imaging). Additionally, to investigate AM indices' correlation with other phenotypic and functional characteristics of HCM. Methods: We included 50 HCM patients (60±16 years, 80% male, maximum wall thickness 18.6±4.1mm) without history of AF who have consecutively undergone 2D-speckle tracking echocardiography and cardiovascular magnetic resonance (CMR) with late gadolinium enhancement (LGE). TACT and LARS measurement is shown on left panel. Burden of fibrosis (percentage of LV mass) was defined by LGE extent (>5 standard deviations compared to nulled myocardium) in CMR slices. Cut-off points for TACT, LAVI and LARS were adopted by literature (≥115 msec, ≥34 mL/m 2 and <21.3% respectively). Results: All HCM patients had preserved EF (61.8±8%), while 13 (26%) presented outflow tract obstruction and 4 (8%) diastolic dysfunction stage≥2. LGE was observed in 32 patients (64%) occupying 7.2±5% of left ventricular (LV) mass. Mean TACT was 139.9±22 msec, with LAVI being 30.8±16.1 mL/m 2 and LARS 27.6±13.9%. After assessing prevalence of AM parameters, 41 patients (82%) presented a prolonged (≥115 msec) TACT with only 13 of them having also a significantly dilated LA (≥34 mL/m 2 ) and 16 an impaired LARS. Among HCM demographic, phenotypic and functional characteristics tested, age and LV mass index were found to be the only independent regressors of TACT (r=0.54, p<0.0005 and r=0.44, p=0.002 respectively, right panels), while E/E' (r=−0.44, p=0.003) and fibrosis extent (r=0.36, p=0.02) were the strongest predictors of LARS and LAVI values respectively. Conclusions: Atrial electro-mechanical delay assessed through TDI based TACT, is the most frequent AM parameter among HCM patients irrespective of AF and even before LA dilatation and LA strain impairment. AM parameters seem to correlate with various morphological and functional characteristics of HCM, their significance, however, in predicting progression towards AF development or HF presentation remains to be elucidated. Funding Acknowledgement: Type of funding sources: None.